The Importance of Destination Image and Tourist Self-Congruity in Increasing Intention to Visit: A Case Study on Generations Y and Z at the Seaweed Tourism Destination in Nusa Penida, Bali - Ni Wayan Merry Nirmala Yani; Puspita, Ni Putu Lianda Ayu; Virginiya, Putu Tika (Jurnal Ilmiah Manajemen & Bisnis, 2024)
This research aimed to examine the relationships among destination image, self-congruity, and visiting intention, as well as the complementary mediating role of self-congruity between destination image and visiting intention. Using a questionnaire as the primary data collection instrument, the study included a sample of 397 participants from Generations Y and Z in Bali, selected through simple random sampling. Data were analyzed using first-order path analysis with structural equation modeling (SEM) in SmartPLS software. The results indicate that self-congruity plays a complementary mediating role between destination image and visiting intention. Additionally, destination image has a significant positive effect on self-congruity, which in turn positively influences visiting intention. These findings contribute to the Theory of Planned Behavior by providing insights into the relationships between destination image, self-congruity, and visiting intention, thereby reinforcing the theory’s underlying principles. From a practical standpoint, this research offers valuable insights for tourism industry stakeholders, aiding in the refinement of destination management and the development of more effective marketing strategies. Understanding the mediating role of self-congruity can help stakeholders identify specific areas for improvement to attract more visitors.